Sustainable Tourism Development in the Policy Network Concep in Pangandaran Regency - Ilhami, Rizky; Hutama, M Rizky Ganda; Herdiyanto, Mahesa; Gandari, Kintan (GoAcademica Research & Publishing, 2025)
This study analyzes sustainable tourism development in Pangandaran Regency from a policy network perspective. Tourism is an important economic sector that contributes significantly to the local economy, but also presents challenges in environmental and social aspects. The growth of the tourism sector in Indonesia, especially after the pandemic, has shown a significant contribution to national GDP. However, this growth is also accompanied by challenges in various aspects such as economic, environmental, and socio-cultural. Existing regulations such as the Regulation of the Minister of Tourism and the West Java Regional Regulation have established a framework for sustainable tourism development, but still need evaluation and review, especially in Pangandaran Regency which is highly dependent on the tourism sector. This study uses a descriptive-qualitative approach to explore the roles of actors in the policy network, including the government, private sector, local communities, and non-governmental organizations. The results show that cross-sector collaboration in the policy network contributes to tourism through supportive regulations, empowerment, and environmentally-based community development strategies. However, there are still challenges in coordination and integration policies that need to be addressed to improve the effectiveness of sustainable tourism management.